KUALITAS PELAYANAN KESEHATAN IBU HAMIL DAN BERSALIN TERHADAP KEPATUHAN MENGGUNAKAN SARANA KESEHATAN DI WILAYAH KERJA PUSKESMAS TELAGA BIRU - Hartati Inaku; Ibrahim Paneo (program studi ilmu keperawatan fakultas ilmu kesehatan universitas muhammadiyah gorontalo, 2021)
The Influence of Maternal and Maternity Health Care Quality toward Compliance in Using Health Facility at Telaga Biru Health CenterThe aims of this research was to determine the influence of the quality of maternal and maternity health care toward compliance in using health facilities at Telaga Biru Health Center. The design of research was used correlational descriptive and used purposive sampling with a sample of 49 people. The Result showed that respondents who answered good quality of ANC is 25 respondents (51.0%), respondents who answered good quality of labor treatment is 20 respondents (40.8%), and respondents who used the health facilities is 27 respondents (55,1%). Obtained significant correlation coefficient (r) = 0.76, which means there was the influence maternal and maternity health care quality toward compliance in using health facilities at Telaga Biru Health Center.